Technical Feasibility of TachoSil Application on Esophageal Anastomoses - Leonie Haverkamp; Jelle P. Ruurda; Richard van Hillegersberg (Gastroenterology Research and Practice)
Purpose. Sealing esophageal anastomoses with a sealant patch (TachoSil) containing human fibrinogen and thrombin may improve mechanical strength. The aim was to evaluate the technical feasibility of the application of a sealant patch in upper gastrointestinal surgery. Methods. In total 15 patients, 18–80 years old, undergoing thoracolaparoscopic esophagectomy with esophagogastrostomy or laparoscopic total gastrectomy with esophagojejunostomy was included. Different techniques of anastomotic TachoSil patch application were tested and recorded on video. Results. TachoSil was successfully applied to the esophagogastrostomy (n=11) and to the esophagojejunostomy (n=4). A median of 2 (1–6) attempts was necessary to reach successful application. The median duration was 7 (3–26) minutes before successful application was accomplished. The best technique in esophagectomy was the application of TachoSil with the use of 2 cellophane sheets. For total gastrectomy, the patch was folded into a harmonica shape and wrapped around the esophagojejunostomy. Although not significant, the number of attempts and time to success showed a decreasing trend along with the increased experience. Conclusion. Application of TachoSil as a sealant of esophageal anastomoses was technically feasible. Future studies may investigate the value of TachoSil application on the prevention of anastomotic leakage.